Understanding the China-Tanzania Malaria Control Project: lessons learned from a multi-stakeholder qualitative study - Sun, Zhishan; Zhou, Hui; Chen, Fumin; Lu, Shenning; Liang, Huan; Wan, Erya; Tao, Zecheng; Zhao, Hanqing; Zhou, Xiaonong; Yang, Fan; Wang, Duoquan; Zhang, Xiaoxi (Frontiers in Public Health, 2023)
Background Tanzania is among the countries with the highest malaria cases and deaths worldwide, where vulnerable populations have been severely affected due to poverty and weakness in health system and infrastructure. The China-Tanzania Malaria Control Project (the Project) was a two-phase global health intervention project implemented between 2015 and 2021 that aimed to transfer project-designated intervention experience in malaria elimination to the Tanzanian health system. This study aims to identify the barriers and facilitators encountered during the Project and to improve our understanding of the emerging phenomenon of South-South global health collaboration. Methods We conducted thematic analysis of qualitative data collected from a purposive sample of 14 participants from multiple stakeholders including project management office, project implementation agency, funding partners and external evaluators of the Project. A conceptual framework was developed to construct the interviews guides. The interviews were transcribed verbatim, crossover checked, translated into English, and analyzed with NVivo 12.0. We conducted the open coding followed by the axial coding based on the Grounded Theory to generate themes and subthemes, and identified key influencing factors that aided or hindered the malaria control in Tanzania. Results The findings suggested that malaria control strategies should largely be tailored due to varied socioeconomic contexts. The perceived enablers in practice include project-designated intervention experiences and technologies, professional and self-learning capabilities of the implementation team, sustainable financial assistance, and support from the international partners. The barriers include the shortage of global health talents, existing gaps to meet international standards, defects in internal communication mechanisms, inadequacy of intergovernmental dialogue, and limitations in logistical arrangements. A checklist and policy implications for China's future engagement in malaria control in resource-limited settings have been proposed. Conclusions The initiative of Health Silk Road has generated strong global interest in promoting development assistance in health. In the hope of generalizing the evidence-based interventions to high malaria-endemic countries in Africa, the need for China to carefully face the challenges of funding gaps and the lack of support from recipient governments remains ongoing. It is recommended that China should form an institutionalized scheme and sustainable funding pool to ensure the steady progress of development assistance in health.